A emergência da necessidade formativa docente no campo discursivo da formação de professores no Brasil - Yamashiro, Carla Regina Caloni [UNESP] (2014)
This paper is related to the research area “Public Policies, School Organization and Teachers Training”. Its aim is to study the emergency of the subject teachers training needs in the teachers training discursive field in Brazil. This interest emerged from readings of Michel Foucault’s texts about the relation between the production of knowledge and the exercise of power and their effects on the subjectivation of the individual and the regulation of the population; and from readings about discourse production as an arena of the exercise of power and government strategies. This research has as problem the status of de thruth from the teachers training needs. This research has as its general aim to understand the conditions that provide the emergency of the teachers training needs in the discursive field of the teachers training in Brazil. The specific aims are to identify, describe and analyze the regimen of truth produced by the discourse of the educational policies, specifically the policies about teachers continuous training in Brazil, which put the analysis in the order of the discourse of teachers training policies; and to comprehend the effect of the biopolitics power over the discourse of the current teachers training policies in Brazil...